KESESUAIAN TARIF RETRIBUSI ATAS PEMANFAATAN LAHAN HUTAN MANGROVE KAWASAN TAMAN HUTAN RAYA NGURAH RAI - Premananda, Wayan Hari; Primajana, Dewa Jati (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2023)
Adjustments to levy rates for land use carried out in Tahura Ngurah Rai Area are carried out to obtain tariffs that are in accordance with current conditions. The levy rate is determined by calculating the economic value generated by the Mangrove Forest in Tahura Ngurah Rai area. Assessment of nature using monetary units will show the economic value of the environment so that policy makers can make the right decision between preserving nature or advancing the economy. The purpose of this study was to identify the functions and benefits of Tahura Ngurah Rai mangrove forest and calculate the total economic value of Tahura Ngurah Rai mangrove forest. Tahura Ngurah Rai mangrove forest has three main functions, namely: biological, physical and economic functions. The economic value of the mangrove forest in Tahura Ngurah Rai area obtained using the total economic value method is IDR 72,020,018,026 per year or IDR 52,586,361 per hectare per year. The total economic value is obtained by adding up the direct use values, indirect use values, option value, existence value and inheritance value (bequest value). Keywords: Economic Valuation, Mangrove Forest, Economic Value, Total Economic Value.